2011
DOI: 10.1016/j.forsciint.2010.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Medical examiner and medical toxicologist agreement on cause of death

Abstract: Poisoning is a significant public health threat as the second leading cause of injury-related death in the US. Disagreements on cause of death determination may have widespread implications across several realms of public health including policy and prevention efforts, interpretation of the poisoning literature, epidemiologic data analysis, medical-legal case outcomes, and individualized autopsy interpretation. We aimed to test agreement between the cause of death determined by the medical examiner (ME) and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…Determining a cause of death, particularly in cases of drug toxicity, is sometimes difficult 30. The 19 cases where drugs were considered to have been contributory to deaths attributed to natural disease were not included in further analysis, meaning that our results may underestimate this problem of drug deaths involving oxycodone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Determining a cause of death, particularly in cases of drug toxicity, is sometimes difficult 30. The 19 cases where drugs were considered to have been contributory to deaths attributed to natural disease were not included in further analysis, meaning that our results may underestimate this problem of drug deaths involving oxycodone.…”
Section: Discussionmentioning
confidence: 99%
“…In other instances the pathologist did not mention the contribution of drugs to the cause of death, despite the presence of potentially lethal levels reported in toxicology results. Discordance in opinion between forensic toxicologists and pathologists in establishing a cause of death in cases involving poisoning has been reported in the USA 30. The panel therefore included representation from a range of forensic specialisations including a pathologist, toxicologist, epidemiologist, and public health physician.…”
Section: Methodsmentioning
confidence: 99%
“…The implications of discordance may also affect the way in which medical examiners determine poisoning as the cause of death, placing more emphasis on analysis of the clinical course of the patient. It has been reported that medical examiners and medical toxicologists may disagree on as many as 34% of cases in which poisoning was suspected as the cause of death [8]. It has also been suggested that collaboration between the RPCC and the medical examiners office may enhance the accuracy of identifying poisoning related fatalities, presumably by providing a more in-depth analysis of the clinical course of the patient [9].…”
Section: Discussionmentioning
confidence: 99%
“…Intoxications represent a significant public health threat [1]. In the United States of America, intoxications appear as the second leading cause of injury-related death, only surpassed by motor vehicle collisions [2].…”
Section: Introductionmentioning
confidence: 99%
“…In the United States of America, intoxications appear as the second leading cause of injury-related death, only surpassed by motor vehicle collisions [2]. The World Health Organization (WHO) considered poisoning amongst the top 15 causes of death for individuals ages 5-44 years old and estimated that 99% of the intoxication related fatalities occur in developing countries [1,3]. According to the 2013 Annual Report of the American Association of Poison Control Center, 2,113 cases of fatal intoxications were registered.…”
Section: Introductionmentioning
confidence: 99%